HIV and COVID-19 epidemics: Does viral coexistence impact the course of clinical entities? A Narrative literature review (Research, Society and Development, 2023)
Introduction: A syndemic is characterized as a situation in which two or more diseases interact in such a way as to cause greater damage than the mere sum of the two diseases. In this sense, cases of co-infection between SARS-CoV-2 and HIV can be interpreted in this way. Objective: The aim of this study was to understand the viral coexistence of SARS-CoV-2 with HIV and to detail the consequences of the overlap of these two viruses on the course of the clinical entities of patients with this co-infection. Materials and Methods: This is an integrative literature review on the general clinical characteristics of SARS-CoV-2 co-infection in HIV patients. The PICO strategy was used to develop the guiding question. In addition, the descriptors "HIV"; "COVID-19"; "Coinfection" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The studies show that SARS-CoV-2 co-infection involves specific nuances within medical analysis, including interactions between antiretroviral therapies and the immune response, challenges regarding diagnosis and treatment, and even its implications for public health. Conclusion: Both COVID-19 and HIV/AIDS are extremely serious health problems that humanity has been facing for some time. The situation is even worse when HIV patients contract the respiratory virus, and resources need to be mobilized quickly to combat the diseases simultaneously.